Use of an electromagnetic-guided device to assist with post-pyloric placement of a nasoenteral feeding tube: A systematic review and meta-analysis - Mancini, Fabio Catache; de Moura, Diogo Turiani Hourneaux; Funari, Mateus Pereira; Ribeiro, Igor Braga; Neto, Fernando Lopes Ponte; Mendieta, Pastor Joaquin Ortiz; McCarty, Thomas R.; Bernardo, Wanderley Marques; Nahas, Sergio Carlos; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2022)
Background and study aims While endoscopic-guided placement (EGP) of a post-pyloric nasoenteral feeding tube may improve caloric intake and reduce the risk of bronchoaspiration, an electromagnetic-guided placement (EMGP) method may obviate the need for endoscopic procedures. Therefore, the primary aim of this study was to perform a systematic review and meta-analysis of randomized trials comparing the efficacy and safety of EMGP versus EGP of a post-pyloric feeding tube.Methods Protocolized searches were performed from the inception through January 2021 following PRISMA guidelines. Only randomized controlled trials were included comparing EMGP versus EGP. Study outcomes included: technical success (defined as appropriate post-pyloric positioning), tube and patient associated adverse events (AEs), time to enteral nutrition, procedure-associated cost, and procedure time. Pooled risk difference (RD) and mean difference (MD) were calculated using a fixed-effects model and heterogeneity evaluated using Higgins test (I2).Results Four randomized trials (n = 536) were included. A total of 287 patients were included in the EMGP group and 249 patients in the EGP group. There was no difference between EMGP versus EGP regarding technical success, tube-related AEs, patient-related AEs, procedure time, and time in the right position. Time to enteral nutrition favored EMGP (MD: –134.37 [–162.13, –106.61]; I2 = 35 %); with significantly decreased associated cost (MD: –127.77 ($) [–135.8–119.73]; I2 = 0 %).Conclusions Based on this study, EMGP and EGP were associated with similar levels of technical success and safety as well as time to complete the procedure. Despite this, EMGP was associated with reduced cost and time to initiation of nutrition.